Obstacles and sustainability of enhanced recovery after surgery in pediatric laparoscopic pyeloplasty - Zhu, Wenliang; Lai, Huajian; He, Ziqin; Zhang, Yifei; Guo, Qiang; Zhong, Wenwen; Ye, Lei; Qiu, Jianguang; Wang, Dejuan (Frontiers in Pediatrics, 2024)
Objectives: Previous studies on Enhanced Recovery After Surgery (ERAS) in pediatric Laparoscopic Pyeloplasty (LP) lacked clear control cases and discussed the obstacles in the implementation process. This article details the obstacles and lessons learned during the implementation of ERAS in patients with ureteropelvic junction obstruction (UPJO).Methods: An ERAS protocol was implemented in the UPJO population undergoing LP, which included preoperative, intraoperative, and postoperative management. The clinical data of ERAS program Before Implementation (BI) and After Implementation (AI) were collected and analyzed retrospectively.Results: A total of 107 patients (BI 46, AI 61) were enrolled. Compared with the BI group, the AI group had an earlier normal diet (19.83h vs 9.53h, p<0.001), ambulation (39.10h vs 12.70h, p<0.001), resumption of defecation (89.88h vs 27.90h, p<0.001), less need for additional analgesia (19.5% vs 1.6%, p=0.002) and shorter postoperative hospital stay (POS) (6.00d vs 1.91d, p<0.001) without increasing complications and readmission rates.Patients in the AI group had a median protocol score of 17 (IQR 16-18), and the compliance rate of the ERAS protocol was negatively correlated with the length of POS (R 2 =0.69, p<0.001).The application of ERAS in pediatric LP is feasible and sustainable, with the potential for even greater impact as compliance improves. Common barriers were uncertain start time of surgery, lack of knowledge of ERAS among pathway participants, and support from anesthesiologists. Pre-determining the start time of surgery, strengthening preoperative education and positive communication among team members can help to promote the full implementation of ERAS program.